Evaluating training adaptation with heart-rate measures: a methodological comparison - Plews, D. J.; Laursen, P. B.; Kilding, A. E.; Buchheit, M. (International Journal of Sports Physiology and Performance, 2013)
The aim of this study was to compare 2 different methodological assessments when analyzing the relationship between performance and heart-rate (HR) -derived indices (resting HR [RHR] and HR variability [HRV]) to evaluate positive adaptation to training. The relative change in estimated maximum aerobic speed (MAS) and 10-km-running performance was correlated to the relative change in RHR and the natural logarithm of the square root of the mean sum of the squared differences between R-R intervals on an isolated day (RHRday; Ln rMSSDday) or when averaged over 1 wk (RHRweek; Ln rMSSDweek) in 10 runners who responded to a 9-wk training intervention. Moderate and small correlations existed between changes in MAS and 10-km-running performance and RHRday (r = .35, 90%CI [-.35, .76] and r = -.21 [-.68, .39]), compared with large and very large correlations for RHRweek (r = -.62 [-.87, -.11] and r = .73 [.30, .91]). While a trivial correlation was observed for MAS vs Ln rMSSDday (r = -.06 [-.59, .51]), a very large correlation existed with Ln rMSSDweek (r = .72 [.28, .91]). Similarly, changes in 10-km-running performance revealed a small correlation with Ln rMSSDday (r = -.17 [-.66, .42]), vs a very large correlation for Ln rMSSDweek (r = -.76 [-.92, -.36]). In conclusion, the averaging of RHR and HRV values over a 1-wk period appears to be a superior method for evaluating positive adaption to training compared with assessing its value on a single isolated day.